Mensius Tentang Persahabatan dan Relevansinya - Lelung, Weldi (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2024)
Mencius placed true friendship as an important element in human life. He emphasized the importance of friendship based on moral principles and goodness. In his view, friendship is not based solely on personal gain or interest, but rather on sincerity, mutual respect, and good intentions to help each other achieve virtue. According to Mencius, humility, mutual respect, supporting each other in the pursuit of virtue, and conformity of values ​​between individuals are the main foundations of true friendship. True friendship is seen as an important element for the formation of strong moral character, the creation of harmony in society, and personal development towards wisdom and moral perfection. Furthermore, Mencius also emphasized that true friendship is not just a reciprocal relationship, but is also a means for individuals to remind each other and improve themselves in pursuing virtue. This research provides valuable insight into the concept of friendship in the Confucian tradition which is still relevant in the current era. True friendship also reflects the realization of a sensitive and reflective heart as taught by Mencius.